La relación entre 'Fas' e `Ius' en la romanística contemporánea : substratos ideológicos de un debate sobre la relación entre religión y estado - Flores, Alfredo de Jesus Dal Molin (2014)
The author presents through this work the relationship between religion and law in ancient Rome, in order to provide an additional element of analysis for a deeper understanding of secularism and the juridical phenomenon today. For this, it is necessary to observe the evolution of the idea among authors, which is initially presented in the form of an opposition between two concepts, wich eventually derive into a distinction, and Þ nally to a complementation.